Plant Growth-Promoting Bacteria Allowed Saving N and N2O Emissions Without Yield Penalties in Sugarcane - Chalco Vera, Jorge Elías; Valencia-Molina, Manuel C.; Carrizo, Manuel; Vassallo, Gianina; Alfaro, Julio D.; Acreche, Martin Moises (Springer, 2025)
Using plant growth-promoting bacteria (PGPB) in cropping systems could be a promising practice to mitigate nitrous oxide (N2O) emissions. However, for sugarcane, a crop with high nitrogen (N) demand, the effect of PGPB on those emissions remains uninvestigated. This study investigated the effects of PGPBs on N2O emissions, early-stage crop growth, yield, and yield components. We followed the static chamber method to measure N2O emissions, and the initial crop growth was assessed using Gompertz models. The treatment with Pseudomonas fluorescens strain Ps6 plus Azospirillum argentinense sp. nov. strain Az39T (PsAz) increased by 40% the maximum number of primary shoots emerged (p = 0.0035) at the plant cane. For the 1st ratoon crop, combining this treatment with half of the traditional N-fertilized dose increased the mean number of stalks per linear meter and showed a tendency to increase crop yield by 15%. Peaks of N2O emissions were only present for the N-fertilized treatments in both years. Inoculated treatments produced, on average, lower cumulative N2O emissions than the traditional N-fertilized treatments. This study demonstrated that PGPB can prevent increased N2O emissions without affecting crop yield.